2015 IEEE 14th International Conference on Machine Learning and Applications (ICMLA) 2015
DOI: 10.1109/icmla.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

What to Learn Next: Recommending Commands in a Feature-Rich Environment

Abstract: Despite an abundance of commands to make tasks easier to perform, the users of feature-rich applications, such as development environments and AutoCAD applications, use only a fraction of the commands available due to a lack of awareness of the existence of many commands. Earlier work has shown that command recommendation can improve the usage of a range of commands available within such applications. In this thesis, we address the command recommendation problem, in which, given the command usage history of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Software engineering researchers and practitioners are often frustrated by the low adoption of practices and tools, such as static analysis, refactoring tools, program comprehension, or security testing, even though many of them are generally perceived to be beneficial. Researchers have found a wide range of technical and social pain points in tool adoption, such as false positives in static analysis tools [e.g., 39,64,71], missing trust in correctness [e.g., 74], crypting tool messages [e.g., 38,39], slow response times [e.g., 80], lack of workflow integration [e.g., 36,41,64,86], lack of collaboration support [39], lack of management buy-in [e.g., 18,80], overwhelming configuration effort [e.g., 25,36,39,71,80], and simply a lack of knowledge about tools [e.g., 60,74,87]. In response, most software engineering research has focused on technical solutions, such as improving functionality, accuracy, and performance [e.g., 8,64,72], improving usability [e.g., 38,46,51,72,79], and improving discoverability through recommendation mechanisms or process integration [e.g., 49,64,87].…”
Section: Theory and Related Workmentioning
confidence: 99%
“…Software engineering researchers and practitioners are often frustrated by the low adoption of practices and tools, such as static analysis, refactoring tools, program comprehension, or security testing, even though many of them are generally perceived to be beneficial. Researchers have found a wide range of technical and social pain points in tool adoption, such as false positives in static analysis tools [e.g., 39,64,71], missing trust in correctness [e.g., 74], crypting tool messages [e.g., 38,39], slow response times [e.g., 80], lack of workflow integration [e.g., 36,41,64,86], lack of collaboration support [39], lack of management buy-in [e.g., 18,80], overwhelming configuration effort [e.g., 25,36,39,71,80], and simply a lack of knowledge about tools [e.g., 60,74,87]. In response, most software engineering research has focused on technical solutions, such as improving functionality, accuracy, and performance [e.g., 8,64,72], improving usability [e.g., 38,46,51,72,79], and improving discoverability through recommendation mechanisms or process integration [e.g., 49,64,87].…”
Section: Theory and Related Workmentioning
confidence: 99%
“…Murphy-Hill et al [9] used six algorithms based on command popularity and collaborative filtering, by taking into account command executions histories. Zolaktaf and Murphy [12] suggested CoDis, which is based on command discovery patterns and co-occurrence of executions in sessions. Silva et al [11] performed static source code analysis to identify and rank opportunities for refactoring command executions.…”
Section: B Algorithms For Ide Command Recommender Systemsmentioning
confidence: 99%
“…• CoDis 6 : the algorithm that performed best in the offline study reported by Zolaktaf and Murphy [12]; and…”
Section: Long-term User Studymentioning
confidence: 99%
See 2 more Smart Citations